Energy and Sugar Content of Ready-To-Drink Tea and Coffee Marketed in South Tangerang, Indonesia - Yustiyani, Yustiyani (Media Gizi Indonesia, 2024)
Excessive sugar consumption, primarily through sugar-sweetened beverages, has been linked to the occurrence of type 2 diabetes mellitus (T2DM). The Ministry of Health of Indonesia recommends that the maximum sugar consumption for the general population not exceed 50 g per day. One type of sugar-sweetened beverage that has been massively distributed in Indonesia is ready-to-drink (RTD) tea and coffee. This study examined the energy and sugar content of the RTD coffee and tea marketed in the modern retail market and their contribution to the Indonesian recommended dietary allowance. This study was conducted in June 2022. Ready-to-drink (RTD) coffee and tea were purchased from five supermarkets and three minimarkets in South Tangerang City, Banten, Indonesia. Data obtained from the product label was recorded and then analysed descriptively. 47 coffee (17 brands) and 58 tea (20 brands) products were obtained during the survey. Most coffee (55.3%) and tea (86.2%) products are distributed in plastic bottles. The median serving size of coffee (240 mL) is slightly smaller than that of tea (250 mL). On average, one serving size of coffee and tea products contributes to 35.7% and 34.8% of the recommended dietary allowance of sugar, respectively. Consumers are advised to take caution while consuming RTD coffee and tea products as they might contribute to excessive sugar consumption. The government must impose regulations to limit sugar content in food and beverage products and increase consumer education to reduce sugar consumption, especially sugar-sweetened products.